(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The article examines institutional factors influencing startup commercialization in Uzbekistan under the conditions of digital transformation. The empirical basis consists of comparative evidence from Startup Survey 2024 Uzbekistan and Startup Survey 2026 Uzbekistan, which covered 310 startups and 400 startup founders respectively. The analysis shows that the Uzbek startup ecosystem is becoming more structured: the share of full-time founder involvement increased, two-member teams became more common, venture fund participation expanded, and trust in investors improved. At the same time, most projects remain at the idea and MVP stages, while only a limited share reaches sales. The article argues that the key development problem is not the shortage of entrepreneurial ideas, but the weak conversion of ideas into validated products, customers, revenue and investment readiness. The proposed institutional response is a coordinated support pipeline combining incubation, mentoring, legal and accounting services, customer validation, MVP testing, investor-readiness programs and regional startup infrastructure. The article also proposes an econometric logic for assessing startup development outcomes through founder characteristics, team capacity, sector, region, access to finance, mentoring, legal support and investor trust.